Three Arguments to Support International Binding Treaty on Business and Human Rights - Surya Oktaviandra (Badan Strategi Kebijakan Hukum, 2022)
The development of the promotion and protection of human rights, in general, has been gladdening. However, in instances where human rights are affected by business activity, efforts to uphold them meet certain obstacles. This is exacerbated when the business activity involves a complex and international dimension in it